Perception of outdoor environments while listening to music: the mutual influence of music and environmental features - Franěk, Marek; Režný, Lukáš (Psychological research, 2024)
This study explored the effects of music on the perception of outdoor urban environments, both built and natural. The participants (n = 74) evaluated five environments located on one walking route in terms of emotional and spatio-cognitive dimensions while listening to one of two types of music: upbeat and conventional or reflective and complex. We found only a very slight effect of music on the evaluation of the emotional and spatio-cognitive dimensions of the environment. The less complex upbeat and conventional music increased the perceived complexity of environments but only if participants took the route from less complex to more complex environments. The liking music mediated the effect of music in the evaluation of emotional dimensions of the environment. Furthermore, a less-liked environment negatively affected the liking of music heard in that environment. Reflective and complex music was perceived as more congruent with the environment than upbeat and conventional music, which is explained by musical fit theory. The features of the environments that were evaluated had a stronger effect on listeners than the music. Natural environments were perceived as more coherent, mysterious, pleasant, interesting, and energetic than built environments, regardless of the music. Moreover, a contrast effect was observed in which the features of the first environment evaluated influenced the evaluation of subsequent environments. It is suggested that the intensity of music may be an important factor for environmental evaluations, in addition to the specific situations in which the music is heard.
Keywords: Environment; dospělí; Emotions; Female; Music; Adult; mladý dospělý; hudba; ženské pohlaví; Adolescent; emoce; lidé; Auditory Perception; sluchová percepce; Male; Young Adult; životní prostředí; mužské pohlaví; mladiství; Humans